22 years later, what is the future for the South Door of Expo ‘98?: Lisbon (1994-1998) - Vieira, E. J. (2022)
This project combined the desire for representation and symbolism characteristic at the entrance to Expo ‘98 with the recovery of an industrial structure of significant impact. With the creation of a support building at the base, simulating a shipwreck, it was possible to fulfil the requirements and integrate the Cracking Tower into the entrance. With this, the Cracking Tower has remained an effective memory of the area, and it should also become a privileged viewpoint of the entire new space open to the north. In the 22 years after Expo ‘98, little use has been made of the building, and it has remained closed and without public access. We are currently witnessing an attempt to return this space to the community; however, it depends on the assessment requested from the LNEC on the structural integrity of the edifice. This article aims to recap the design process and construction of this industrial structure as it was integrated into a building. The goal is to return it to the public and, preferably, allow access to the top of the Tower. It is a striking building in the local landscape.